Lucrècia Borja. L'alteració d'una identitat i l'errònia atribució de la pintura de Flora de Bartolomeo Veneto. - VICO, ALEXANDRE (Scripta, 2017)
This study intended to emphasize the identity has been wrong that has reached our days of Lucrezia Borgia and the wrong attribution has been made of some pictures. One of the most paradigmatic paintings is Flora (c.1520), painted by artist Bartolomeo Veneto. This work has gone down in history as one indissoluble portrait of Lucrezia, but recent studies have shown represents an ideal model influenced by the literary context probably related to Pietro Bembo. During the Renaissance, portraits represent much more than a specific and mimetic identity. They are supports of prestige and ideological transmission, of moral virtues, memory, etc. In the Venetian art scene of the early sixteenth century, multiple female portraits often difficult to identify that criticism have related courtesans, mistresses, wives. Many of these paintings also represent poetic ideals through which painting demonstrate its ability to compete with poetry in terms of demonstrating the aesthetic ideal of beauty. This short paper aims to examine the successive historiographical interpretations erroneously identified the painting of Flora with Lucrezia Borgia due to the erotic value related to her pejoratively, but also wants to highlight other proposals that have allowed the work to be performed with the most appropriate exegesis.